Perspectives on the Technological Aspects and Biomedical Applications of Virus‐Like Particles/Nanoparticles in Reproductive Biology: Insights on the Medicinal and Toxicological Outlook. Issue 8 (29th May 2022) - Chandrasekar, Vaisali; Singh, Ajay Vikram; Maharjan, Romi Singh; Dakua, Sarada Prasad; Balakrishnan, Shidin; Dash, Sagnika; Laux, Peter; Luch, Andreas; Singh, Suyash; Pradhan, Mandakini
Abstract : Increasing data on the infection indicate that maternal infections are severe. Under the realms of vaccine development, virus‐like particles (VLP)/nanoparticles (NPs) hold the promise of targeted control of therapeutics transfer across the placental barrier with the potential to trigger innate immune responses. Though the placenta is known to act as a barrier against exogenous materials, viruses exploit the transport systems and overcome the barrier properties. VLPs can be strategically designed to obtain the necessary mechanisms for navigation across the placenta and immune response. However, several knowledge gaps on the chemical, viral transmission strategies and the host defense response exist owing to the highly dynamic etiology of the placental barrier. This further complicates the toxicological analysis of the developed therapeutics. Herein, placental physiology and functions are discussed in significance with chemical toxicology, viral infections, and the host defense. Further, the promising applications of VLPs and perspective on their design to overcome the placental gatekeeper to gain the necessary immune response or therapy are provided. Finally, a holistic approach to various bioengineering models for studying chemical toxicants, viral infections, and effects of VLPs is provided to facilitate better translation of these VLPs to clinical applications. Abstract : Herein, placental physiology and functions are discussed in significance with chemical toxicology, viral infections, and the host defense. Further, the promising applications of virus‐like particles and perspective on their design to overcome the placental gatekeeper to gain the necessary immune response or therapy are provided.